Industrial Organic Chemistry - Benvenuto, Mark Anthony (De Gruyter textbook., 2017)
Industrial Organic Chemistry examines all major industrial manufacturing technologies and reaction types with a focus on organic chemistry in general and petroleum refining in particular. The author takes a systematic approach to introducing the most impo.